The Personality Potion - MacDonald, Alan (Oxford Oxford University Press, 2014)
In The Personality Potion Danny is scared to audition for a part in the school play. His Uncle Hal gives him a magic potion, it is green and fizzy and full of stars and it works wonders. Or does it? TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Magic -- Readers (Elementary) -- Afrikaans language